2022
DOI: 10.3390/ijms23031270
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dorsomedial Hypothalamus GABAergic Neurons in Sleep–Wake States in Response to Changes in Ambient Temperature in Mice

Abstract: Good sleep quality is essential for maintaining the body’s attention during wakefulness, which is easily affected by external factors such as an ambient temperature. However, the mechanism by which an ambient temperature influences sleep–wake behaviors remains unclear. The dorsomedial hypothalamus (DMH) has been reported to be involved in thermoregulation. It also receives projection from the preoptic area, which is an important region for sleep and energy homeostasis and the suprachiasmatic nucleus—a main con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…EEG/EMG electrode implantation surgery. EEG recordings and analysis were performed as previously described 54,55,56 . Under pentobarbital sodium anesthesia (50 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…EEG/EMG electrode implantation surgery. EEG recordings and analysis were performed as previously described 54,55,56 . Under pentobarbital sodium anesthesia (50 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Like most hypothalamic nuclei, the DMH comprises a heterogeneous population of neurons, but the subpopulation(s) of DMH neurons that regulate locomotor activity rhythms are not fully understood. Locomotor activity rhythms are unaffected by chemogenetically activating or genetically ablating GABAergic DMH neurons but are abolished when leptin receptor-expressing DMH neurons are genetically silenced [ 162 , 163 ]. Activating mWake -, brain-derived neurotrophic factor (BDNF)-, or prodynorphin-expressing DMH neurons each acutely increases locomotor activity.…”
Section: Outputs From the Scn: Behavioral Rhythmsmentioning
confidence: 99%
“…Disruption of GABAergic neurons in the LHA dysregulates sleep and induces vigorous eating habits. A study looked at GABAergic neurons in the DMN region of the mouse hypothalamus and found that these neurons play a role in sleep–wake changes elicited by exposure to warmth in mice, indicative of their role in maintaining sleep and energy homeostasis [ 221 ].…”
Section: Perspectives and Future Work In The Fieldmentioning
confidence: 99%